Compound semiconductor nanowires for optoelectronic device applications - Gao, Q; Joyce, H; Paiman, S; Kang, J; Tan, H; Jagadish, C; Jackson, H; Smith, L; Yarrison-Rice, J; Zou, J (2011)
We review GaAs and InP nanowires and GaAs based nanowire heterostructures grown on (111)B substrates by metal organic chemical vapor deposition via vapor-liquid-solid (VLS) mechanism. Transmission electron microscopy, time-resolved photoluminescence and micro-Raman spectroscopy have been used to understand the crystal structure, carrier lifetime and strain effects on the bandgap energy. © 2011 IEEE.